The determination of rents in shopping centers during recession period in Lithuania - Raslanas, Saulius; Lukošienė, Indrė (International Journal of Strategic Property Management, 2013)
This research examines how to relieve the economical pressure to the market of shopping centers by choosing one of the percentage rent forms. Retail rents have two rental components typically: base rent and overage rent, which is equal to some predetermined percentage on sales and is paid once the tenant reaches some level of sales. Both of these components are related to many factors which are considered in international practice. The determination of the percentage rents in Lithuania is much more complicated because the most important information about retail segments of the shopping centers (sales per square meter, gross leasable area and rental prices) is not publicly available. The goal of this research was to analyze the US experience and data that is available on percentage rent determination and to adapt it to the Lithuanian market by implementing required adjustments. First Publish Online: 23 Sep 2013